HUBUNGAN TINGKAT PENGETAHUAN DENGAN KECEMASAN DALAM MENCEGAH PAPARAN CORONA VIRUS DISEASE (COVID-19) DI PERKOTAAN - Ahmad Guntur (LPPMK STIKES Widyagama Husada, 2021)
Background: Coronavirus disease (covid-19) is one of the new types of viruses that appeared at the end of 2019. This virus is known to be very dangerous compared to previous viral viruses, the signs and symptoms of coronavirus (covid-19) are fever of more than 38C, cough and shortness of breath. In general, the anxiety experienced by each individual is caused by knowledge factors. Lack of knowledge about coronavirus (covid-19) can cause a person to panic and worry about his health. Objective: the purpose of this study is to find out the relationship between the level of knowledge and public anxiety on the prevention of coronavirus disease (covid-19) in Mojolangu Subdistrict Lowokwaru, Malang Method In this research using quantitative type that is descriptive correlative, with cross sectional approach. Measuring instruments in this study using questionnaire Zung Self Anxiety Rating Scale and public knowledge in preventing covid 19. The research sample was 171 respondents and the research was conducted in Mojolangu district, Malang City with the test used is somers'd test. Results: Of the 171 respondents, 109 respondents had good knowledge (63.7%), 22 respondents had moderate knowledge (12.9%) and 40 respondents had less knowledge (23.4%) and for public anxiety obtained From 171 respondents, as many as 16 respondents experienced severe anxiety (9.4%), 28 respondents experienced moderate anxiety (16.4%) and 127 respondents experienced mild anxiety (74.2%). The large value of correlation between knowledge level and public anxiety in dealing with coronavirus disease (covid-19) in Mojolangu Sub district Lowokwaru Malang amounted to -0.345 which showed a negative correlation with the strength of moderate correlation. Conclusion There is a relationship between the level of knowledge and public anxiety in the face of coronavirus disease in Mojolangu district lowokwaru Malang. Keywords: Knowledge level; anxiety; coronavirus disease (covid-19